2023
DOI: 10.3390/pharmaceutics15051405
|View full text |Cite
|
Sign up to set email alerts
|

Topical Delivery of Ketorolac Tromethamine via Cataplasm for Inflammatory Pain Therapy

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) have been widely used in the treatment of inflammatory pain, such as in osteoarthritis. Ketorolac tromethamine is considered to be an NSAID with strong anti-inflammatory and analgesic potency, however, traditional applications, such as oral administration and injections, often induce high systemic exposure, leading to adverse events such as gastric ulceration and bleeding. To address this key limitation, herein we designed and fabricated a topical delivery system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…More recent literature offers interesting examples of PAA-based systems implemented in topical drug delivery. However, in these cases, PAA was mainly used as a viscosity enhancer, requiring different excipients [ 54 ] or cross-linking [ 55 ] to maintain the structural stability and integrity of the formulation. In contrast, PAAbCH is versatile by combining its attributes to simplify formulation composition.…”
Section: Resultsmentioning
confidence: 99%
“…More recent literature offers interesting examples of PAA-based systems implemented in topical drug delivery. However, in these cases, PAA was mainly used as a viscosity enhancer, requiring different excipients [ 54 ] or cross-linking [ 55 ] to maintain the structural stability and integrity of the formulation. In contrast, PAAbCH is versatile by combining its attributes to simplify formulation composition.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the regulation of respiratory activity, the PBN projects to the nucleus tractus solitarius (NST), preBöt complex, rostral ventral respiratory group (rVRG), etc. [7,35]. In pain regulation, the PBN mainly projects to the CeA, BNST, PAG, intralaminar thalamic nucleus (ILN), ventral tegmental area (VTA), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pain is one of the major contributors to the health care burden and is associated with many chronic diseases [5,6]. Despite the high prevalence and severity of inflammatory pain, the medications currently available to treat inflammatory pain are unsatisfactory, such as nonsteroidal anti-inflammatory drugs (NSAIDs), opioids and some adjuvant medications [7]. The combination of different drugs with different mechanisms of action improves the therapeutic effect, but their use is limited due to their increased risk of side effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in clinical settings, pharmacotherapy for fungal keratitis includes effective antifungal agents combined with anti-inflammatory medications. , These includes the use of topical natamycin, amphotericin B, fluconazole, voriconazole aided with dexamethasone, diclofenac, and ketorolac like NSAIDs. In a prospective clinical study, voriconazole was identified as an effective and well-tolerated drug for the management of stubborn corneal ulcers resulting from Aspergillus keratitis . However, severe inflammatory FK often associated with corneal wounds which progresses to ulcers and eventually leaves corneal scar which leads to vision impairment. ,, Corneal scarring stands as a primary contributor to the loss of corneal transparency and resultant blindness on a global scale .…”
Section: Introductionmentioning
confidence: 99%